Direct mapping of the electric permittivity of heterogeneous non-planar thin films at gigahertz frequencies by scanning microwave microscopy. Issue 5 (20th January 2017) - Biagi, Maria Chiara; Badino, Giorgio; Fabregas, Rene; Gramse, Georg; Fumagalli, Laura; Gomila, Gabriel
Abstract : We obtained maps of electric permittivity at ∼19 GHz frequencies on non-planar thin film heterogeneous samples by means of combined atomic force–scanning microwave microscopy (AFM–SMM). Abstract : We obtained maps of electric permittivity at ∼19 GHz frequencies on non-planar thin film heterogeneous samples by means of combined atomic force–scanning microwave microscopy (AFM–SMM). We show that the electric permittivity maps can be obtained directly from the capacitance images acquired in contact mode, after removing the topographic cross-talk effects. This result demonstrates the possibility of identifying the electric permittivity of different materials in a thin film sample irrespectively of their thickness by just direct imaging and processing. We show, in addition, that quantitative maps of the electric permittivity can be obtained with no need for any theoretical calculation or complex quantification procedures when the electric permittivity of one of the materials is known. To achieve these results the use of contact mode imaging is a key factor. For non-contact imaging modes the effects of local sample thickness and of the imaging distance make the interpretation of the capacitance images in terms of the electric permittivity properties of the materials much more complex. The present results represent a substantial contribution to the field of nanoscale microwave dielectric characterization of thin film materials with important implications for the characterization of novel 3D electronic devices and 3D nanomaterials.